2018
DOI: 10.1121/1.5023834
|View full text |Cite
|
Sign up to set email alerts
|

A method for testing the wide-sense stationary uncorrelated scattering assumption fulfillment for an underwater acoustic channel

Abstract: Wide-sense stationary and uncorrelated scattering (WSSUS) assumptions are often applied for the statistical description of wireless communication channels. However, in the case of underwater acoustic channels the WSSUS model is of limited value. The degree of similarity of in-phase and quadrature components of the channel impulse response, measured with the use of bandpass modulated signals, can be used as an indicator of WSSUS assumption fulfillment. The paper describes an experimental method that uses quadra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In [14] the method of testing, if the impulse response measured with the probe signal s(t) satisfies the assumption of WSS, it is presented. It is based on testing the similarity of the autocorrelation functions:…”
Section: Testing Wide-sense Stationary Assumption Fulfilmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14] the method of testing, if the impulse response measured with the probe signal s(t) satisfies the assumption of WSS, it is presented. It is based on testing the similarity of the autocorrelation functions:…”
Section: Testing Wide-sense Stationary Assumption Fulfilmentmentioning
confidence: 99%
“…In [14], a novel time-domain method for verifying the WSS feature of UAC channels is described. Statistical properties of the real and imaginary parts of the impulse response, measured using the correlation method, are exploited to test the WSS assumption fulfilment.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that, in addition to the noise level, the range and accuracy of bearings also depend on noise correlation (Rudnicki et al, 2020). The problem also applies to detection in underwater acoustic communications UAC (Kochańska et al, 2018;Schmidt et al, 2018). Active, narrow-band systems typically assume that acoustic ambient noise is uncorrelated (Burdick, 1984;Urick, 1983;1986).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the signals transmitted in UAC systems suffer from time-variability of multipath propagation conditions (Kochańska et al, 2016). Moreover, a UAC channel cannot always be described as wide-sense stationary with uncorrelated scattering (WSSUS), as is commonly assumed in the case of radio-communication channels (Kochańska et al, 2018;Sklar, 1997).…”
Section: Introductionmentioning
confidence: 99%